2022
DOI: 10.1038/s41598-022-18483-3
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of orbital angular momentum and polarization through biological waveguides

Abstract: A major roadblock to the development of photonic sensors is the scattering associated with many biological systems. We show the conservation of photonic states through optically self-arranged biological waveguides, for the first time, which can be implemented to transmit light through scattering media. The conservation of optical properties of light through biological waveguides allows for the transmission of high bandwidth information with low loss through scattering media. Here, we experimentally demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…At similar laser power and sample preparation conditions to the previous Gaussian beam experiments, an optical vortex beam with orbital angular momentum can also form stable waveguides at different wavelengths. The vortex beam preserves its donut shape and orbital angular momentum in RBC suspensions over several centimeters distance (Figure 2) [14]. In addition, both Gaussian and vortex beams are capable of nonlinear coupling into waveguide channels and both preserve their orbital angular momentum and intensity distribution [14].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At similar laser power and sample preparation conditions to the previous Gaussian beam experiments, an optical vortex beam with orbital angular momentum can also form stable waveguides at different wavelengths. The vortex beam preserves its donut shape and orbital angular momentum in RBC suspensions over several centimeters distance (Figure 2) [14]. In addition, both Gaussian and vortex beams are capable of nonlinear coupling into waveguide channels and both preserve their orbital angular momentum and intensity distribution [14].…”
Section: Resultsmentioning
confidence: 99%
“…The vortex beam preserves its donut shape and orbital angular momentum in RBC suspensions over several centimeters distance (Figure 2) [14]. In addition, both Gaussian and vortex beams are capable of nonlinear coupling into waveguide channels and both preserve their orbital angular momentum and intensity distribution [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that under certain conditions, the transmittance of LG beams in certain biological tissues and scattering media is higher than that of ordinary lasers [16][17][18] . Due to the scattering and biological tissue characteristics of Chlorella fluid, we also tested its transmittance using several different types of light sources.…”
Section: Harnessing Spin and Orbital Angular Momentum Light For Optim...mentioning
confidence: 94%